An Empirical Analysis of the Growth of Indian Derivative Market - Upputuri, Sreelekha; Prasad, M.S. V; Sri, Sandhya (The journal of contemporary issues in business and government, 2021)
The term risk is a characteristic feature of most commodity and capital markets. Variations in the prices of agricultural and non-agricultural commodities are induced, over time, by demand- supply dynamics. The last two decades have witnessed many-fold increase in the volume of international trade and business due to the wave of globalization and liberalization sweeping across the world. This has led to rapid and unpredictable variations in financial assets prices, interest rates and exchange rates, and subsequently, to exposing the corporate world to an unwieldy financial risk. In the present highly uncertain business scenario, the importance of risk management is much greater than ever before. The emergence of derivatives market is an ingenious feat of financial engineering that provides an effective and less costly solution to the problem of risk that is embedded in the price unpredictability of the underlying asset. India’s experience with the equity derivatives market has been extremely positive over the years. The Study conducted has been an attempt to analyse the derivative market over the years and an analysis and a comparative study of the NSE and BSE has been attempted with the help of percentage analysis, trend and CAGR.